Effects of 24 Months of Treatment With Romosozumab Followed by 12 Months of Denosumab or Placebo in Postmenopausal Women With Low Bone Mineral Density: A Randomized, Double‐Blind, Phase 2, Parallel Group Study. (22nd May 2018) - McClung, Michael R; Brown, Jacques P; Diez‐Perez, Adolfo; Resch, Heinrich; Caminis, John; Meisner, Paul; Bolognese, Michael A; Goemaere, Stefan; Bone, Henry G; Zanchetta, Jose R; Maddox, Judy; Bray, Sarah; et al.
ABSTRACT: Over 12 months, romosozumab increased bone formation and decreased bone resorption, resulting in increased bone mineral density (BMD) in postmenopausal women with low BMD (NCT00896532). Herein, we report the study extension evaluating 24 months of treatment with romosozumab, discontinuation of romosozumab, alendronate followed by romosozumab, and romosozumab followed by denosumab. Postmenopausal women aged 55 to 85 years with a lumbar spine (LS), total hip (TH), or femoral neck T ‐score ≤–2.0 and ≥–3.5 were enrolled and randomly assigned to placebo, one of five romosozumab regimens (70 mg, 140 mg, 210 mg monthly [QM]; 140 mg Q3M; 210 mg Q3M) for 24 months, or open‐label alendronate for 12 months followed by romosozumab 140 mg QM for 12 months. Eligible participants were then rerandomized 1:1 within original treatment groups to placebo or denosumab 60 mg Q6M for an additional 12 months. Percentage change from baseline in BMD and bone turnover markers (BTMs) at months 24 and 36 and safety were evaluated. Of 364 participants initially randomized to romosozumab, placebo, or alendronate, 315 completed 24 months of treatment and 248 completed the extension. Romosozumab markedly increased LS and TH BMD through month 24, with largest gains observed with romosozumab 210 mg QM (LS = 15.1%; TH = 5.4%). Women receiving romosozumab who transitioned to denosumab continued to accrue BMD, whereas BMD returned toward pretreatment levels with placebo. With romosozumab 210 mg QM, bone formation marker P1NP initially increased after treatment initiation and gradually decreased to below baseline by month 12, remaining below baseline through month 24; bone resorption marker β‐CTX rapidly decreased after treatment, remaining below baseline through month 24. Transition to denosumab further decreased both BTMs, whereas after transition to placebo, P1NP returned to baseline and β‐CTX increased above baseline. Adverse events were balanced between treatment groups through month 36. These data suggest that treatment effects of romosozumab are reversible upon discontinuation and further augmented by denosumab. © 2018 The Authors Journal of Bone and Mineral Research published by Wiley Periodicals, Inc.